European Hospitality Without a Home - Mireille Rosello (Studies in 20th & 21st Century Literature, 2002)
How do European governments conceptualize what they call "hospitality" when they draft immigration laws and when they allow the concepts of asylum, of illegal immigrants, to change according to a constantly evolving political context? What consequences…
Keywords: European hospitality; asylum; illegal immigrants; politics; regional identity; ethnic identity; cultural identity; political hospitality; ethical hospitality; commercial hospitality; guest; host; invitation; parasites; hostages; Didier Van Couwelaert; Un aller simple; a One Way Ticket